Studi Literatur: Analisis Penerapan Model Pembelajaran Bilingual di Sekolah Dasar - Maulidia, Awalina Farhatul; Anastasya, Puspa Ayu; Yuserna, Djenar Mahesa Ayu; Nurfadila, Ratih; Putri, Linda Amelia; Nafiah, Lailatun; Widagdo, Arif (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze various bilingual learning models implemented in primary schools and evaluate their effects on students learning outcomes and communication skills. Through a literature review of journals, books, and scientific documents, it was found that bilingual learning models such as submersion, structured immersion, transition, enrichment immersion, cooperative bilingual, and Communicative Language Teaching (CLT) each present unique advantages and challenges. The transition model and cooperative bilingual model are considered most suitable for primary school students, as they take into account children's linguistic, cognitive, and psychosocial development. The analysis reveals that implementing bilingual learning has a positive impact on language proficiency, critical thinking skills, and students' confidence in using a foreign language, particularly English. However, several challenges hinder effective implementation, including limited teacher proficiency in both languages, varying student language abilities, and a lack of teaching resources and professional training. Therefore, effective implementation strategies, systemic school support, and the development of adaptive bilingual models are necessary to enhance the quality of primary education in Indonesia. This study is expected to contribute to the development of more effective and contextually relevant bilingual teaching practices.